Las Tic para mejorar la enseñanza aprendizaje de matemática, alumnos del séptimo grado, Escuela Educación Básica Municipal “Edgar Vicente Garrido Jaramillo”. Loja - Muñoz Vélez, Jamil Fabricio (2024)
The research that deals with: ICT to improve the teaching and learning of mathematics, seventh grade students, “Edgar Vicente Garrido Jaramillo” Municipal Basic Education School. Loja, for which we worked with the following general objective: Determine the influence of ICT to improve the learning of mathematics in seventh grade students of the Edgar Vicente Garrido Jaramillo Municipal Basic Education School in the city of Loja. period 2023; the same one that allowed me to know if the teacher uses ICT in teaching and learning mathematics; Therefore, the following methods were used: scientific, observational, descriptive, deductive, analytical, synthetic, inductive and statistical, all these methods were used to collect scientific information to subsequently have a criterion of how the teacher is working in terms of the use of ICT as a strategy to improve teaching learning of mathematics in seventh grade students; Likewise, we worked with 28 students and 1 teacher, adding a population of 29 human talents, with the information acquired it helped me obtain conclusions and recommendations. It is concluded that the use of ICT through the Canva tool as a teaching-learning strategy will allow the development of skills to teach and reinforce the resolution of mathematical problems, since through it plays a leading role in motivating the student. , through a wide range of mechanisms to encourage students to participate and, above all, build their own learning, giving a personal meaning to what they learn; Likewise, the teacher must improve his educational actions in terms of the implementation of the Canva tool that leads the student to show interest in learning and thus the teaching is not improvised or traditional.